CREATIVITY IN IMPROVING PROFESSIONAL AND PEDAGOGICAL SKILLS OF PHYSICAL EDUCATION TEACHERS - Uraimov Sanjar; Husanov Doston (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In this article, information on the development of creativity of physical education teachers and the development of willful, intellectual, active, but also personal qualities and physical health, as well as physical health, creativity, initiative, mental potential, is highlighted..